Penerapan Etika Ekosentrisme dalam Pengelolaan Lahan Kopi di Lombok - Aida Muspi'ah; M. Sarjan; Husnul Jannah (Mataram University, 2026)
This study examines the application of ecocentric ethics in coffee land management in Lombok as an effort to understand the relationship between humans and nature within the context of sustainable agriculture. The ecocentric paradigm places nature at the center of moral value, recognizing that every element of the ecosystem has intrinsic worth and the right to maintain its balance. Using a literature review method, this research analyzes scientific publications and empirical studies related to coffee farming practices in Lombok. The objectives of the study are: (1) to examine how ecocentric values are implemented in coffee land management systems; (2) to assess the relationship between environmental ethics and agricultural sustainability; and (3) to highlight the importance of ecological awareness in maintaining a balance between human needs and environmental conservation. The findings indicate that coffee farmers in Lombok have applied ecocentric principles through practices such as agroforestry systems, the use of organic fertilizers, soil and water conservation, and environmentally friendly waste management. These ethical values contribute not only to environmental preservation but also to strengthening the social and economic sustainability of farmers. Furthermore, ecological awareness has developed through community empowerment processes, sustainable leadership, and the integration of local wisdom into agricultural activities. Overall, this study affirms that the implementation of ecocentric ethics in Lombok reflects an agricultural paradigm that balances moral, ecological, and economic dimensions and may serve as a model for ecologically just agricultural development in other regions.